Efforts to Improve Student Learning Outcomes Through The Two Stay-Two Stray (TS-TS) Type Cooperative Learning Model In Class VI Mathematics Subjects At SDN 108384 Lubuk Pakam - Hasibuan, May Fitriana (Journal of Classroom Action Research, 2024)
This research was carried out with the aim of improving the mathematics learning outcomes of class VI students at SDN 108384 LubukPakam by implementing the Two Stay-Two Stray (TS-TS) Cooperative learning model. This research is classroom action research. The data collection techniques used are conducting reviews, data collection and observation. The data collected is a test of student learning outcomes carried out in the third cycle, using the Cooperative Two Stay-Two Stray (TS-TS) method. From the analysis of the data obtained, it can be concluded that there is a significant increase in learning outcomes after learning using the Cooperative Two Stay-Two Stray (TS-TS) method. It can be seen from the average value (mean) of test I, which is 70.31, which is smaller than the average value (mean) of test II, namely 77.34. In test III, the average value (mean) was 86.90, which means that improvement with each test carried out. So we can know that learning using the Cooperative Two Stay-Two Stray (TS-TS) method can improve the mathematics learning outcomes of class VI students at SDN 108384 LubukPakam on the subject of operations to calculate mixed fractions. Keywords: Learning Results, Fractions, Cooperative Type Two Stay-Two Stray (TS-TS)